Valoração econômica da praia de Alter do Chão, Santarém, Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Tourism is a global economic activity, which generates employment, income and currency at a particular location. In the seaside village of Alter do Chão, district of the municipality of Santarém, Pará, the economic dynamics are systematized by activities related to this tertiary sector. The seasonal dynamics of the Tapajós river change the landscape and the local tourist offer, which in the dry and full months the beach emerges and submerges, respectively. In this sense, the objective of this research is to assess a monetary value to this beach, through the Total Economic Valuation (TEV) method, as the main practical application of neoclassical instruments. To address the overall objective, the Thesis is structured into four chapters, each of which corresponds to an article. The first one pointed out the importance of the seasonal dynamics of Alter do ground beach for the tourism economy and the potential socioeconomic impacts on the Alter do Chão seaside resort, to be caused by the implementation of large infrastructure projects, planned within the watershed. ; The second chapter analyzed the occurrence of the tourist phenomenon and its local socioeconomic impact. the third established a relation of time, space, solar factor, precipitation factor and level factor of the Tapajós river, to calculate the carrying capacity, by segmenting into periods of beach level ebb and flow, and finally estimated Alter do Chão beach TEV, by summing up the calculation of the Direct Use Value and Indirect Use Value, during the flood and dry periods. The relevance of the theme derives from a broad investigation on the interaction environment, society and development. The approach of this study is interdisciplinary, as it works with economic concepts in a socioenvironmental context, to which support an analysis on the importance of the quality, use and usefulness of the natural environment, for the development of tourism activity in an Amazonian community. In this sense, it is considered the importance of the environmental factor and its interference in the landscape, attractions and tourist activities in Alter do Chão, for periods throughout the year, to subsidize public policies, strategic planning and local management which consider their peculiarities. improve service delivery, infrastructure, visitor satisfaction and promote economic development in the Alter do Chão community. And the estimated TEV for this natural asset makes it possible to create an indicator, which provides support for decision-making in local social and environmental management to maintain the conserved natural resource, as well as a reference to guide compensatory and restorative measures, in case of eventual conversion into indemnities.
Keywords: Dinâmica Sazonal; Economia do Turismo; Capacidade de Carga; Valor Econômico dos Recursos Ambientais; Rio Tapajós (PA); CNPQ::CIÊNCIAS SOCIAIS APLICADAS; IMPÁCTOS AMBIENTAIS E SOCIAIS DA MUDANÇA DO USO DA TERRA NA AMAZÔNIA